Prevalence and correlates of postpartum PTSD following emergency cesarean sections: implications for perinatal mental health care: a systematic review and meta-analysis - Eirini Orovou; Evangelia Antoniou; Ioannis Zervas; Antigoni Sarantaki (BMC Psychology)
Abstract Background The increasing awareness of the emotional consequences of emergency cesarean deliveries (C-sections) highlights their substantial role in fostering postpartum post-traumatic stress disorder (PTSD). This systematic review and meta-analysis aim to evaluate the prevalence and determinants of PTSD following emergency C-sections, as well as the implications of these events on maternal mental health and welfare. Methods Undertaking extensive searches of Scopus, PubMed, PsycINFO, and Google Scholar, we have incorporated studies published from 2013 onwards that examined the occurrence of PTSD following emergency C-sections. Our primary focus was on the prevalence of PTSD at 6 weeks and up to 12 months postpartum. To evaluate the quality of these studies, we employed the Newcastle-Ottawa Scale (NOS) and the CEBM Critical Appraisal Tools. Findings We included a total of 10 studies with 4,995 participants. The prevalence of PTSD following emergency C-sections ranged from 2.2 to 41.2%, compared to 0–20% in elective cesarean sections. A meta-analysis revealed a significant rise in the number of people with PTSD in the emergency C-section group compared to the elective C-section group six weeks after giving birth (OR = 2.74; 95% CI = 1.13 to 6.64; p = 0.03) and six weeks to 12 months later (OR = 3.68; 95% CI = 2.63 to 5.15; p < 0.00001). The emergency C-section group also had a higher PTSD prevalence compared to vaginal birth six weeks to 12 months after birth (OR 3.16; 95% CI 1.51 to 6.60; p = 0.02). Risk factors included poor social support, maternal and neonatal complications, and prior psychiatric history. Conclusions Emergency C-sections are significantly associated with an increased risk of postpartum PTSD, necessitating targeted psychological support and interventions. Future research should aim for standardized diagnostic criteria and explore the long-term psychological outcomes of emergency C-sections.